Plasma density over Svalbard during the ISBJØRN campaign. - Van Eyken, A.P.; Hall, Chris; Svenes, K.R. (European Geophysical Society, 2000)
In 1997, reliable operation of the EISCAT Svalbard Radar (ESR) was achieved and a rocket launching facility at Ny Ålesund on Svalbard (79°N, 12°E) (SVALRAK) was established. On 20 November, 1977, the first instrumented payload was launched from SVALRAK. Although the payload configuration had been flown many times previously from Andøya Rocket Range on the Norwegian mainland, this presented an unprecedented in situ determination of positive ion density over Svalbard. Simultaneously, ESR measured similar density profiles but in a higher altitude regime. We have combined the ESR measurements with ionosonde data to establish a calibration and subsequently combined the ground-based and in situ determined profiles to give a composite positive ion density profile from the mesosphere to the thermosphere.